Evaluating the accessibility of public service facilities to tourists and residents in island destinations: Evidence from the Changhai County - Zheng, Xiaoling; Zhao, Dong (Frontiers in Public Health, 2023)
The sustainable development goals propose building a people-oriented city, which requires a scientific evaluation of the current allocation of urban public service facilities. With the increasing diversity of social groups, public service facilities need to meet the diverse needs of different groups. However, there is still a lack of in-depth research evaluating urban public service facilities for diverse groups. Therefore, this paper delimits the research area based on data on the temporal and spatial behavior of islanders and tourists, and use urban network analysis (UNA) toolbox to evaluates the public service facilities of the spatially overlapping area from the aspects of facility accessibility and availability. The study shows that (1) the spatial dislocation between facilities and residential places is serious, which leads to redundant construction or a lack of configuration of facilities in some areas. (2) The public service facilities in some areas can be used by tourists and residents to a similar degree, the number of facilities accessible to residents and tourists within a certain distance is not much different, and the configuration of facilities is relatively reasonable. (3) The overall configuration of infrastructure is biased toward residents, but the configuration of facilities in some areas can also reflect group fairness. With the increase in contact and communication between different groups, conducting an evaluation and analysis of public service facilities for different groups holds great significance for the construction of human-oriented urbanization.